2006
DOI: 10.1093/jn/136.9.2399
|View full text |Cite
|
Sign up to set email alerts
|

Design of Optimal Food-Based Complementary Feeding Recommendations and Identification of Key “Problem Nutrients” Using Goal Programming

Abstract: The WHO is urging countries to promote improved complementary feeding practices to ensure optimal health, growth, and development of young children. To help achieve this, a rigorous 4-phase approach for designing optimal population- specific food-based complementary feeding recommendations (CFRs) was developed and is illustrated here. In phase I, an optimized diet is selected, using goal programming (Model #1), which aims to provide a desired nutrient content with respect to habitual diet patterns and cost. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
157
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 12 publications
1
157
0
2
Order By: Relevance
“…18 Promoting optimal CF practices in developing countries is a global health priority. 19 However, based on previous reports, timely initiation of CF at the 6th month of age in developing countries, such as Ethiopia, Nairobi, and so forth, was usually under 50%. 20 This study first reported the feeding behaviors of children in Myanmar and found inappropriate feeding behaviors that resulted in malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…18 Promoting optimal CF practices in developing countries is a global health priority. 19 However, based on previous reports, timely initiation of CF at the 6th month of age in developing countries, such as Ethiopia, Nairobi, and so forth, was usually under 50%. 20 This study first reported the feeding behaviors of children in Myanmar and found inappropriate feeding behaviors that resulted in malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…A facilidade de avaliação multifatorial, usando técnicas de modelagem matemática, amplia a gama de conhecimentos para o pesquisador porque fornece ferramentas capazes de correlacionar múltiplos fatores, que no caso da nutrição e alimentação inclui os hábitos alimentares dos indivíduos, as quantidades de nutrientes presentes nas dietas e alimentos, fatores econômicos e culturais das populações de estudo, agricultura local e favorecimento climático para a oferta de alimentos, entre outros 37 . A utilização do delineamento experimental baseado na metodologia de superfície de resposta para misturas foi abrangente e possibilitou a varredura de toda a região estudada na busca da melhor formulação possível, mostrando que os resultados obtidos estão de acordo com a literatura, podendo ser uma ferramenta importante a ser utilizada na terapia nutricional.…”
Section: Discussionunclassified
“…The result obtained showed a marked improvement of the goal programming results over that of linear programming. [8] also developed a 4-phase approach for designing optimal population-specific food-based Complementary Feeding Recommendations (CFRs) in which the goal programming techniques were used to select an optimal diet which aimed at providing a desired nutrient content with respect to habitual diet patterns and cost. A hypothetical example was used to illustrate the approach.…”
Section: Introductionmentioning
confidence: 99%